Comparative Study on Monthly Variations of Traffic-Related Ozone and Its Precursors in High and Low Vehicular Emission Areas: Education Perspective - Idongesit Edem Okon; Elaoyi D. Paul; Idongesit Bassey Anweting; Anthony Abutu Attah; Kahinde Israel Omoniyi; Patricia Adamma Ekwumemgbo (Universitas Pendidikan Indonesia (UPI), 2024)
Emissions from vehicular traffic reduce air quality and increase the concentrations of precursor pollutants (NO2, CO, and VOCs), thus influencing the variation of ground-level O3 in the air. This study compares the monthly variations in concentrations of traffic-related O3 and its precursors in high and low vehicular emission areas, carried out in situ using AeroQUAL 500 portable air analyzer across the three traffic periods [morning peak, off-peak (afternoon), and evening peak] for twelve months. Information on traffic flow was obtained by direct counting. Monthly concentrations of pollutants compared with the Nigerian Ambient Air Quality Standard (NAAQS) limits showed that maximum concentration for NO2 (0.090 ppm), VOCs (1.927 ppm), and O3 (0.063 ppm) were higher than the NAAQS limits of 0.04 – 0.06 ppm, 0.050 ppm and 0.060 ppm for NO2, VOCs and O3 respectively, informing the need to educate people in this area.